Relationship between serum ECP and TIgE levels and the risk of postoperative recurrence in patients with chronic rhinosinusitis with nasal polyps - Zhang, Qing; Li, Hui; Xie, Di; Fan, SiJian (Frontiers in Surgery, 2025)
ObjectiveThis study was undertaken to assess the association between the likelihood of surgical recurrence and serum ECP and TIgE levels in chronic rhinosinusitis with nasal polyps (CRSwNP).MethodologyClinical information was gathered retrospectively from 166 cases of surgically treated CRSwNP as well as 60 cases of chronic rhinosinusitis without nasal polyps (CRSsNP). A comparative analysis on serum levels of total immunoglobulin E (TIgE) and eosinophil cationic protein (ECP) was carried out between the two groups. The CRSwNP patients were assigned into recurrence and non-recurrence groups based on the absence/presence of disease recurrence after a 2-year follow-up. An analysis was conducted on the correlation between the patients' clinical data and their serum ECP and TIgE levels. Receiver operating characteristic (ROC) curves were utilized to assess the clinical utility of these two biomarkers.ResultsThe CRSwNP participants had higher serum levels of ECP and TIgE (4.28 ± 0.81 > 3.58 ± 0.77 ng/L, P < 0.001; 52.99 ± 8.62 > 15.65 ± 3.25 KU/L, P < 0.001) compared to CRSsNP participants. Univariate analysis indicated that neutrophil ratio, lymphocyte ratio, Lund-Kennedy score, Lund-Mackay score, SNOT-22 score, olfactory function score, and postoperative recurrence were significantly correlated with serum ECP and TIgE levels. Higher serum levels of TIgE and ECP (4.89 ± 0.79 < 4.11 ± 0.72, P < 0.001; 58.74 ± 8.27 < 51.40 ± 8.04, P < 0.001) were detected in the recurrence groups vs. the non-recurrence group. Multivariate analysis showed that serum ECP and TIgE were independent risk factors for recurrence of CRSwNP. Serum ECP and TIgE levels were found to be predictive of postoperative recurrence risk in CRSwNP patients (AUC: 0.77, 0.74, 0.84; P < 0.05) according to ROC curve analysis. Significant differences were not observed in any general clinical data.ConclusionThe findings suggest that elevated serum ECP and TIgE levels in patients with CRSwNP can be as good predictors for the risk of recurrence after endoscopic sinus surgery.